Arabic Language Learning with Communicative Method and Factors Affecting Student's Speaking Ability - Azhar, Muhammad; Wahyudi, Hakmi; Promadi, Promadi (MAN 4 Kota Pekanbaru, 2022)
Research on communicative methods for acquiring and teaching a second language has been extensively explored. Still, the research is more dominant on the acquisition and teaching of English only. This study aims to describe learning Arabic by using communicative methods and the factors that influence the Arabic speaking ability of students in the superior class of Darussakinah Batu Bersurat Islamic Boarding School. The method used is the descriptive qualitative method. The results of this study indicate that the use of communicative methods in learning Arabic increases students’ speaking skills, and students actively speak Arabic in the learning process. Other factors that affect students’ speaking ability are the language environment, continuous daily vocabulary, and good mastery of Arabic Grammar (nahwu and shorof grammar). Mastery of Arabic grammar is beneficial for students in reconstructing memorized vocabularies into complete sentences, thus creating a sense of confidence in speaking.